2021
DOI: 10.1038/s41467-021-23587-x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor p53 regulates intestinal type 2 immunity

Abstract: The role of p53 in tumor suppression has been extensively studied and well-established. However, the role of p53 in parasitic infections and the intestinal type 2 immunity is unclear. Here, we report that p53 is crucial for intestinal type 2 immunity in response to the infection of parasites, such as Tritrichomonas muris and Nippostrongylus brasiliensis. Mechanistically, p53 plays a critical role in the activation of the tuft cell-IL-25-type 2 innate lymphoid cell circuit, partly via transcriptional regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 55 publications
(92 reference statements)
1
34
0
Order By: Relevance
“…We previously reported that Jaw1 is localized on the ER and the outer nuclear membrane, and it is associated with nuclear shape maintenance 16 . Furthermore, Jaw1 was recently reported to interact with all ITPR subtypes via its coiled-coil domain, and the deletion of Jaw1 in mouse embryonic fibroblast (MEF) reduces Ca 2+ influx into the cytoplasm upon ionomycin stimulation, a reagent that increases cell membrane ion permeability 13 . However, whether and how Jaw1 is involved in the calcium dynamics under physiological conditions, such as GPCR stimulation-related aspects, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that Jaw1 is localized on the ER and the outer nuclear membrane, and it is associated with nuclear shape maintenance 16 . Furthermore, Jaw1 was recently reported to interact with all ITPR subtypes via its coiled-coil domain, and the deletion of Jaw1 in mouse embryonic fibroblast (MEF) reduces Ca 2+ influx into the cytoplasm upon ionomycin stimulation, a reagent that increases cell membrane ion permeability 13 . However, whether and how Jaw1 is involved in the calcium dynamics under physiological conditions, such as GPCR stimulation-related aspects, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…ETCs also produce and release cysteinyl leukotrienes (CysLTs), potent eicosanoid lipid mediators, in response to N. brasiliensis and H. polygyrus but not Tritrichomonas musculis [57]. Recently, murine ETCs were shown to activate the tumor suppressor gene p53 following N. brasileinsis and Tritrichomonas muris infection [73]. One consequence of this p53 activation was upregulated expression of the lymphoid-restricted membrane protein (LRMP1), which, in association with the channel protein ITPR2 (Inositol 1,4,5-Trisphosphate Receptor Type 2), coordinates the release of Ca 2+ ions and subsequent release of IL-25 via TRPM5 [73].…”
Section: Tuft Cell Contributions To the Th2 Response To Helminthsmentioning
confidence: 99%
“…Recently, murine ETCs were shown to activate the tumor suppressor gene p53 following N. brasileinsis and Tritrichomonas muris infection [73]. One consequence of this p53 activation was upregulated expression of the lymphoid-restricted membrane protein (LRMP1), which, in association with the channel protein ITPR2 (Inositol 1,4,5-Trisphosphate Receptor Type 2), coordinates the release of Ca 2+ ions and subsequent release of IL-25 via TRPM5 [73]. This adds another level of intracellular control over IL-25 to regulate the activation of a Th2 cascade.…”
Section: Tuft Cell Contributions To the Th2 Response To Helminthsmentioning
confidence: 99%
“…IP 3 then binds its cognate receptor IP 2 R in the small intestine or IP 3 R in the airway and causes calcium efflux from the endoplasmic reticulum. Calcium efflux also appears to require interactions between Inositol 1,4,5-Triphosphate Receptor Associated 2 (IRAG2) with IP 3 receptors [ 40 ]. Intracellular calcium flux activates transient receptor potential cation channel subfamily M member 5 (TRPM5), which allows sodium influx and subsequent cellular depolarization.…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptional regulation driving expression of tuft cell signaling components is poorly characterized, but it is known that p53 regulates expression of the transmembrane protein coding gene Irag2 , which is required for calcium flux. Additional molecules that activate tuft cells likely exist that have not been discovered [ 23 , 29 , 31 , 40 , 43 , 47 , 49 55 ]. GNAT3, G Protein Subunit Alpha Transducin 3; GPCR, G protein–coupled receptor; IRAG2, Inositol 1,4,5-Triphosphate Receptor Associated 2; PLCβ2, phospholipase C beta 2.…”
Section: Introductionmentioning
confidence: 99%